Cognitive-Pragmatic Models of Subtext Construction in Texts - Sultonova , Nigora Abduganievna (The Lingua Spectrum, 2026)
This article deals with the issues based on the cognitive–pragmatic models of subtext construction in texts. Subtext is interpreted as a complex interaction between explicit semantic meanings and implicit conceptual structures activated in the reader’s mind. Drawing on theories of cognitive linguistics (conceptual metaphor, mental spaces, frame semantics) and pragmatics (speech acts, implicature, presupposition, inferencing), the study examines how hidden meanings emerge within literary and media discourse. Textual examples illustrate dominant subtext-building mechanisms such as metaphorical coding, ironic presupposition, contextual implicature, and dialogic ambiguity strategies. Findings demonstrate that subtext is a dynamic cognitive process determined by readers’ cultural background, emotional experience, and interpretive competence. The study also emphasizes the role of inferential activity in decoding implicit meanings. The proposed cognitive–pragmatic models contribute to theoretical linguistics, discourse analysis, and translation studies by offering a systematic framework for interpreting implicit textual meanings. In addition, the research addresses how readers actively participate in meaning creation by filling semantic gaps and constructing conceptual associations guided by discourse context. Special attention is given to cross-cultural variation in subtext interpretation and to communicative strategies authors use to manipulate ideological and emotional responses. The proposed cognitive–pragmatic models contribute to theoretical linguistics, discourse analysis, and translation studies by offering a systematic framework for interpreting implicit textual meanings and improving methods for analyzing hidden layers of communication across languages.